Rabaʿ, Muhammad. “The Arabic Era of Protest as Described by Ibn Khaldūn: Linguistic Unity or Duplicity?” Year 3, Issue 12 (Spring 1418-1419 AH/ 1998 CE), Pp. 77-97. - ربّاع, محمّد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1998)
Muhammad Rabaʿ explains the dimensions of the issue of using the Arabic language - the language of the Qur’an - as a reality for evaluation and description, citing evidence indicators which Ibn Khaldūn documented in his Muqaddimah. Rabaʿ considers the Muḍariyyah language as described by Ibn Khaldūn, its time, speakers, characteristics, and its acquisition and learning, to conclude in refuting duplicity and recognition that the unity of the Arabic language in the era of protest is an inspiring model that may be invested for reviving the Arabic language. He concludes, moreover, that Ibn Khaldūn’s thought on language acquisition and learning is a basis to promote classical (fuṣḥā) Arabic language, since his theorization on this issue concords with the results of contemporary linguistic theories.